Strong enhancement of 10–100 keV electron fluxes by combined effects of chorus waves and time domain structures - Qianli Ma; Didier Mourenas; Anton Artemyev; Wen Li; Richard M. Thorne; Jacob Bortnik (Geophysical Research Letters)
Abstract Time domain structures (TDSs) are trains of intense electric field spikes observed in large numbers during plasma injections in the outer radiation belt. Here we explore the question of their importance in energetic electron acceleration and loss in this region. Although the most common TDSs can preaccelerate low‐energy electrons up to 1–5 keV energies, they often cannot produce by themselves the seed population of 30–150 keV electrons, which are needed for a subsequent energization up to relativistic energies during storms or substorms. However, we demonstrate by numerical simulations that modifications of the low‐energy electron pitch angle and energy distributions due to interactions with TDS lead to more efficient scattering of electrons by chorus waves toward both higher and lower pitch angles, ultimately leading to both significantly higher fluxes in the 10–100 keV energy range and more intense 1–100 keV precipitation into the atmosphere, potentially affecting the outer radiation belt dynamics.